2013
DOI: 10.1186/1866-1955-5-14
|View full text |Cite
|
Sign up to set email alerts
|

Working memory deficits in high-functioning adolescents with autism spectrum disorders: neuropsychological and neuroimaging correlates

Abstract: Working memory is a temporary storage system under attentional control. It is believed to play a central role in online processing of complex cognitive information and may also play a role in social cognition and interpersonal interactions. Adolescents with a disorder on the autism spectrum display problems in precisely these domains. Social impairments, communication difficulties, and repetitive interests and activities are core domains of autism spectrum disorders (ASD), and executive function problems are o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
124
1
9

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(147 citation statements)
references
References 103 publications
(115 reference statements)
13
124
1
9
Order By: Relevance
“…Ahissar et al 2006;Ahissar 2007). Restrictions in auditory short-term memory and working memory have indeed been demonstrated in individuals with ASD (e.g., Barendse et al 2013; but see Stanutz et al 2014 for evidence of enhanced pitch memory in ASD) or in individuals with severe language impairment (e.g., Archibald and Gathercole 2006). Yet, in the study of Bhatara et al (2013) the significant 4,000 Hz FD deficit in adolescents with ASD was observed in a fixed reference FD task which may have minimized memory involvement by allowing the construction of a perceptual anchor.…”
Section: Discussionmentioning
confidence: 96%
“…Ahissar et al 2006;Ahissar 2007). Restrictions in auditory short-term memory and working memory have indeed been demonstrated in individuals with ASD (e.g., Barendse et al 2013; but see Stanutz et al 2014 for evidence of enhanced pitch memory in ASD) or in individuals with severe language impairment (e.g., Archibald and Gathercole 2006). Yet, in the study of Bhatara et al (2013) the significant 4,000 Hz FD deficit in adolescents with ASD was observed in a fixed reference FD task which may have minimized memory involvement by allowing the construction of a perceptual anchor.…”
Section: Discussionmentioning
confidence: 96%
“…Our findings are also consistent with previous studies (Barron-Linnankoski et al, 2015;Blair et al 2002;Garcia, 2001;Hooper, Poon, Marcus, & Fine, 2006;Korkman, Kirk, & Kemp, 1998;Minshew and Goldstein 2001;Narzisi et al, 2013;O'shea et al, 2005;Williams, Goldstein, & Minshew, 2006a;Williams, Goldstein, & Minshew, 2006b). Deficits in verbal working memory, difficulties in developing strategies for free recall of information, and difficulties in organizing words and resisting interference are further reasons to favor pictorial information instead of lexical in the interventions and in the teaching materials provided for children with ASD (Bowler, Matthews, & Gardiner, 1997;Barendse et al, 2013;Narzisi et al, 2013).…”
Section: Memory and Learning Domainmentioning
confidence: 99%
“…A aprendizagem requer a manipulação da informação, interação com a memória de longo prazo e, simultaneamente, armazenamento e processamento da informação (Dehn, 2008). Existem evidências extensas na literatura de prejuízos associados a MO e diferentes quadros de transtornos que podem aparecer na infância e adolescência como TDAH, dislexia, síndromes genéticas, problemas de sono, depressão, esquizofrenia, transtorno bipolar, autismo, estresse, entre outros (Barendse, et al 2013;Leutwyler et al 2013;Mervis & Velleman, 2011;Skogan, et al 2013;Talarowska, Zboralski, & Gałecki, 2013;Tucker, 2013;Wang & Gathercole, 2013). A partir dos estudos citados, a MO parece ser uma função chave em muitos quadros que apresentam alterações no desenvolvimento.…”
unclassified